Bioactive coating containing yeast mycocin for the control of blue mold in postharvest apples - Fabiana Fiusa Ferreira; Douglas Rangel da Costa; Laura Fernandes Campos; Lyssa Setsuko Sakanaka; Marianne Ayumi Shirai; Alexandre Rodrigo Coelho (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to evaluate the antifungal effect of a bioactive coating containing Hansenula wingei mycocin on the control of blue mold in post-harvest apples. The bioactive coating (FS+CFE) was prepared with a filmogenic solution (FS) and cell-free extract (CFE) of H. wingei. The bioactive coating was tested in vitro against Penicillium expansum, by measuring conidial germination and hyphal growth inhibition. In situ tests were conducted on apples coated with FS+CFE and stored at 25°C for 12 days, to evaluate the incidence of blue mold rot in apples, the occurrence of wounds infected by P. expansum, the severity of blue mold rot, and the effectiveness of lesion control. Physicochemical parameters such as pH, soluble solids, and mass loss were also analyzed. The coating FS+CFE showed a significant antifungal activity by inhibiting P. expansum conidial germination and hyphal growth, as well as reducing the progression of blue mold rot. Coated apples maintained their physicochemical and physical properties consistent with natural ripening. The bioactive coating with H. wingei mycocin is a promising strategy for controlling P. expansum in postharvest apples.